STRATEGI PENGEMBANGAN PARIWISATA KAWASAN DANAU TOBA - Lazuardina, Annisa; Amalia G, Shabrina; Alif R , Zaki; Syafril R, Lalu (Warta Pariwisata, 2024)
This research aims to identify and formulate development strategies for the Lake Toba Region as a super priority destination in supporting national economic development and equitable distribution of development. The Lake Toba area is a National Strategic Area (KSN) and a National Tourism Destination. The vision and mission of the Lake Toba Region are sustainable development, preservation of diversity, integrated development between districts, increased attractiveness, and sustainable tourism development. The Integrated Tourism Master Plan (ITMP) and the Integrated and Sustainable Tourism Development Program (P3TB) support tourism development in the Lake Toba Region. This research will formulate a comprehensive planning strategy for the Lake Toba Region by considering the territorial integrity and infrastructure supporting tourism. Infrastructure development, including the Tebing Tinggi-Serbelawan toll road, will support the development of the Lake Toba area. This research will contribute to the development of the Lake Toba Region as Indonesia's leading tourism destination.